Retraction Notice - -, - (Jurnal Penelitian dan Pembelajaran IPA, 2018)
Retraction notice to ” The Correlation of Learning Independence Attitudes and Student’s Learning Achievement on Physics Learning Based-Portfolio” [Jurnal Penelitian dan Pembelajaran IPA, vol.3, no.1, 2017, pp. 74–83]Asep Saefullah1, Parsaoran Siahaan2 & Ika Mustika Sari31Department of Science Education, Faculty of Teacher Training and Education,  Universitas Sultan Ageng Tirtayasa2,3Department of Physics Education, Faculty of Mathematics and Natural Science Education, Universitas Pendidikan Indonesia This article has been retracted. The authors have plagiarized part of a paper that had already appeared in WAHANA PENDIDIKAN FISIKA (WAPFI) Vol.1, No.1, Year 2013 in Indonesian Language and available online at http://ejournal.upi.edu/index.php/WapFi/article/view/4891. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.